Monetary policy and stock prices – Cross-country evidence from cointegrated VAR models - Belke, Ansgar; Beckmann, Joscha (Journal of Banking & Finance, 2015)
This study applies the Cointegrated Vector-Autoregressive (CVAR) model to analyze the long-run relationships and short-run dynamics between stock markets and monetary policy across five developed and three emerging economies. Our main aim is to check whether monetary policy plays an important role for stock market developments. As an innovation, monetary policy enters the analysis from three angles: in the form of a broad monetary aggregate, short-term interest rates and net capital flows. Based on this framework, we analyze whether central banks are able to influence stock market developments. Our findings suggest different patterns and causalities for emerging and industrial economies with the stock markets of the former economies more frequently related to monetary aggregates and capital flows. A direct long-run impact from short-term interest rates on stock prices is only observed for 3 out of 8 economies.